Influencing Factors on Taxpayer Compliance: Quantitative Insights from Medan Marelan, North Sumatra - Safitri, Rahmadani; Aisyah, Siti (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This research investigates the influence of tax-related factors on taxpayer compliance in Medan Marelan sub-district. Specifically, it explores the impact of tax sanctions, taxpayer awareness, tax socialization, and the quality of tax services on compliance. Utilizing a quantitative approach, the study involves 100 respondents and employs multiple linear regression tests for data analysis. Questionnaires are distributed to registered taxpayers, and SPSS 22.0 is utilized for data processing. The findings reveal that tax sanctions, taxpayer awareness, tax socialization, and the quality of tax services collectively influence taxpayer compliance. Notably, tax sanctions and taxpayer awareness exhibit positive and significant impacts on compliance, emphasizing the motivational role of threat and the importance of taxpayer understanding. Furthermore, effective tax socialization and quality tax services contribute positively and significantly to compliance, fostering a conducive environment for taxpayers. These results provide comprehensive insights into the factors shaping taxpayer compliance in Medan Marelan sub-district, offering valuable considerations for authorities in crafting tax policies and strategies to enhance compliance.